2018
DOI: 10.2196/11076
|View full text |Cite
|
Sign up to set email alerts
|

Teleconsultation Using Mobile Phones for Diagnosis and Acute Care of Burn Injuries Among Emergency Physicians: Mixed-Methods Study

Abstract: BackgroundThe referral process in acute care remains challenging in many areas including burn care. Mobile phone apps designed explicitly for medical referrals and consultations could streamline the referral process by using structured templates and integrating features specific to different specialties. However, as these apps are competing with commercial chat services, usability becomes a crucial factor for successful uptake.ObjectiveThe aim of this study was to assess the usability of a mobile phone app for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…Among the methods used to evaluate system usability, the methods that involve present users in the real world provide a better understanding of system usability. Previous studies [54][55][56][57] have shown that think aloud method identifies many problems related to usability and identifies the root cause of the problems. Thus, this study used think aloud method to evaluate the application and the identified usability problems were solved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the methods used to evaluate system usability, the methods that involve present users in the real world provide a better understanding of system usability. Previous studies [54][55][56][57] have shown that think aloud method identifies many problems related to usability and identifies the root cause of the problems. Thus, this study used think aloud method to evaluate the application and the identified usability problems were solved.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Ehrler et al [56] showed that appropriate labeling for items can improve the ease of use of the mobile health application. In addition, Klingberg et al [57] found that changes in button design were effective in improving their performance.…”
Section: Resultsmentioning
confidence: 99%
“…The usability of the app has been previously evaluated with South African users, both emergency doctors and burns specialists. 27 In another study by Blom et al, South African burns and emergency care specialists believed the app would streamline the diagnostic process, improve both triage and referrals, and be a more secure option for remote diagnosis compared with current practices. 28…”
Section: The Vula Applicationmentioning
confidence: 99%
“…mHealth is also increasingly used to aid physicians in their medical decision making [ 48 ] and to facilitate consultations with other providers and experts in their areas of expertise [ 49 , 50 ], highlighting the broad applicability of mHealth, not only for patients but also for medical providers. In a survey of health care providers, more than 70% of physicians had smartphones, and 77% of nurses and doctors used medical apps [ 51 ].…”
Section: Introductionmentioning
confidence: 99%